Alice in Borderland. Volume 6 - Aso, Haro, 1980-; Werry, John (Translator) (Viz signature., 2023)
"Eighteen-year-old Ryohei Arisu is sick of his life. School sucks, his love life is a joke, and his future weighs on him like impending doom. As he struggles to exist in a world that can't be bothered with him, Ryohei feels like everything would be better if he were anywhere else. When a strange fireworks show transports him and his friends to a parallel world, Ryohei thinks all his wishes have come true. But this new world isn't an empty paradise, it's a vicious game. And the only way to survive is to play. The battle against the King of Clubs continues as Arisu and his team struggle to make up for their shocking point deficit. But no matter what strategy they try, the king and his compatriots maintain the upper hand. When each move is a matter of life or death and no victory comes without sacrifice, can Arisu and his team bear another loss to secure the win?"--Back cover.